Kualitas Layanan Sebagai Upaya Kepuasan Masyarakat Pemanfaat Media Sosial Dan Sms Center Sebagai Sarana Pengaduan - Mujiono Mujiono (Universitas Islam Kadiri, 2020)
The purpose of this study was to determine the process of handling public complaints through social media and sms center in Blitar City. Testing the significance of the effect of service quality on community satisfaction on social media users and sms center as a means of public complaints in the Office of Public Works and Spatial Planning of Blitar City. Which service quality variable dominantly influences community satisfaction on social media users and sms center as a means of public complaints in the Department of Public Works and Spatial Planning of Blitar City. The research methodology used descriptive questionnaires, interviews and multiple linear regression tests on 5 (five) independent variables namely tangibles X1, X2 reliability, responsiveness X3, assurance X4 and attention (empathy). ) X5 against Y dependent community satisfaction variable. The results of the study concluded that the Guarantee, Physical Evidence, Empathy and Responding variables simultaneously (together) had a significant influence on community satisfaction and spatially only the four variables had an influence on community satisfaction.